ENGLISH DAILY NEWSPAPER AND ITS IMPACT ON PROFESSIONAL LITERACY FOR ENGLISH LECTURER - Jasuli Jasuli (Universitas Muhammadiyah Gresik, 2016)
The present study aims at finding the impacts of English daily newspaper on thedevelopment of professional literacy for lecturer. The literate daily habit of Englishlecturers is the underlying reason why this study is carried out. The literate habits can befound where lecturers used to be reading printed mass media written in English besidesreading other primary textbooks and references. They designate The Jakarta Post massmedia which is the biggest mass media in Indonesia written in English. As the study focuseson how the daily newspaper contributes to their professional literacy, a qualitativedescriptive research design is used to execute the study. The respondents are Englishlecturers of Teacher Training and Education (IKIP) Budi Utomo Malang consisting ofseventeen lecturers. The data is gained through observation and interview. Based on thedata analysis, it is found that English daily newspaper has impacts on lecturers' professionalliteracy. Respondents were challenged to how Indonesian phrases are expressed in English.They are also challenged to be more critical reader, both editing and content critical based.While on their duties of Tridharma, the newspaper is leveraged as classroom supplementsfor teaching language skills and components as well as linguistics and literature studies.Their writing stamina also boosted as their input from the news increased. Finally, theirexperiences are very often expressed in their last Tridharma duties, i.e. public services bysharing and upgrading teachers' literacy at schools.